Operational upgrades to improve traffic flow in Small Middleweight Cities: Windhoek, Namibia - Ntinda, Henock Mankavu (Department of Civil Engineering, 2016)
The study of the improvements to transport controlling facilities, defined in this dissertation as operational transport upgrades, aims to ascertain its influence on a growing urban traffic demand. This dissertation assesses the influence that the conversion of Werner List Street into a one-way street has on the performance of traffic accommodation. Werner List Street links traffic commuting from the south to the north of Windhoek's Central Business District (CBD). The CBD traffic demand is estimated to breach network capacity by 2015, a scenario prevalent in many small middleweight cities. The research conducted a literature review on aspects related to the development and implementation of operational upgrades; thereby gaining an understanding on the relevance that such improvements have on small middleweight cities. Studied literature suggests that with the reduction in the allocation of funds to develop transport systems, transport authorities resort to innovative methods of improving transport network utilising minimal capital expenditure. The limited funding is prevalent in small middleweight cities due to the current lack of major traffic impediment. The research studied aspects of Windhoek's activity system, as presented in the city's Household Survey of 2004 that primarily focused on the income status, transport mode use and transport mode preference. The origin of trips would assist in determining the direction, in relation to Windhoek's CBD, peak traffic commutes.